Specific profiles of new-onset vs. non-inaugural status epilepticus: From diagnosis to 1-year outcome - Benaiteau, Marie; Valton, Luc; Gardy, Ludovic; Denuelle, Marie; Debs, Rachel; Wucher, Valentin; Rulquin, Florence; Barbeau, Emmanuel J.; Bonneville, Fabrice; Pariente, Jérémie; Curot, Jonathan (Frontiers in Neurology, 2023)
While new-onset status epilepticus (NOSE) is a harbinger of chronic epilepsy, prospective medical data are sparse in terms of specifying whether the evolution of status epilepticus (SE) and seizure expression in NOSE resembles what occurs in patients who have already been diagnosed with epilepsy [non-inaugural SE (NISE)] in all aspects apart from its inaugural nature. The aim of this study was to compare the clinical, MRI, and EEG features that could distinguish NOSE from NISE. We conducted a prospective monocentric study in which all patients ≥18 years admitted for SE over a 6-month period were included. A total of 109 patients (63 NISE and 46 NOSE cases) were included. Despite similar modified Rankin scores before SE, several aspects of the clinical history distinguished NOSE from NISE patients. NOSE patients were older and frequently had neurological comorbidity and preexisting cognitive decline, but they had a similar prevalence of alcohol consumption to NISE patients. NOSE and NISE evolve in the same proportions as refractory SE (62.5% NOSE, 61% NISE) and share common features such as the same incidence (33% NOSE, 42% NISE, and p = 0.53) and volumes of peri-ictal abnormalities on MRI. However, in NOSE patients, we observed greater non-convulsive semiology (21.7% NOSE, 6% NISE, and p = 0.02), more periodic lateral discharges on EEG (p = 0.004), later diagnosis, and higher severity according to the STESS and EMSE scales (p < 0.0001). Mortality occurred in 32.6% of NOSE patients and 21% of NISE patients at 1 year (p = 0.19), but with different causes of death occurring at different time points: more early deaths directly linked to SE at 1 month occurred in the NOSE group, while there were more remote deaths linked to causal brain lesions in the NISE group at final follow-up. In survivors, 43.6% of the NOSE cases developed into epilepsy. Despite acute causal brain lesions, the novelty related to its inaugural nature is still too often associated with a delay in diagnosing SE and a poorer outcome, which justifies the need to more clearly specify the various types of SE to constantly raise awareness among clinicians. These results highlight the relevance of including novelty-related criteria, clinical history, and temporality of occurrence in the nosology of SE.